2016
DOI: 10.1155/2016/8549635
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Evaluations of the68Ga-Lissamine Rhodamine B (LRB) as a New Radiotracer for Imaging Tumors by Positron Emission Tomography

Abstract: Purpose. The aim of this study is to synthesize and evaluate 68Ga-labeled Lissamine Rhodamine B (LRB) as a new radiotracer for imaging MDA-MB-231 and MCF-7 cells induced tumor mice by positron emission tomography (PET). Methods. Firstly, we performed the radio synthesis and microPET imaging of 68Ga(DOTA-LRB) in athymic nude mice bearing MDA-MB-231 and MCF-7 human breast cancer xenografts. Additionally, the evaluations of 18F-fluorodeoxyglucose (FDG), as a glucose metabolism radiotracer for imaging tumors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…72–81 Small molecule heterocyclic cations were also used as vehicles to deliver other compounds to mitochondria. 8292 The heterocyclic cations have been conjugated with quinone, spin traps, or thiol-reactive moieties to specifically localize those compounds in cell mitochondria. It was demonstrated that the uptake of rhodamine-linked compounds can be further increased by the addition of the lipophilic tetraphenylborate anion.…”
Section: Approaches To Target Compounds To Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…72–81 Small molecule heterocyclic cations were also used as vehicles to deliver other compounds to mitochondria. 8292 The heterocyclic cations have been conjugated with quinone, spin traps, or thiol-reactive moieties to specifically localize those compounds in cell mitochondria. It was demonstrated that the uptake of rhodamine-linked compounds can be further increased by the addition of the lipophilic tetraphenylborate anion.…”
Section: Approaches To Target Compounds To Mitochondriamentioning
confidence: 99%
“…Many small molecule lipophilic cations (e.g., rhodamine, pyridinium, and cyanine derivatives) have been shown to accumulate in cell mitochondria. Rhodamine- and cyanine-based cationic fluorophores have been extensively used as research tools as mitochondrial stains and for monitoring mitochondrial membrane potential, as discussed below, based on the extent of their total cellular uptake or the ratio of mitochondrial to cytosolic concentration of the cationic probe. Small molecule heterocyclic cations were also used as vehicles to deliver other compounds to mitochondria. The heterocyclic cations have been conjugated with quinone, spin traps, or thiol-reactive moieties to specifically localize those compounds in cell mitochondria. It was demonstrated that the uptake of rhodamine-linked compounds can be further increased by the addition of the lipophilic tetraphenylborate anion .…”
Section: Approaches To Target Compounds To Mitochondriamentioning
confidence: 99%
“…These xanthene based dyes, which exhibit excellent spectroscopic characteristics such as large molar extinction coe cient, high emission quantum yield, absorption and emission at longer wavelengths, are therefore tuned to facilitate in vitro and/or in vivo monitoring of various chemical and biological species exploiting their contrast structure-function relation. The uorescence output of Fluorescein type dyes is pH sensitive and bleaches quickly, thus, its applicability gets restricted in a variety of applications (Li et al 2016). On contrary, rhodamine based dyes become a preferable choice as labelling agents considering the tuneable uorescence output, and ease of synthesis and functionalisation.…”
Section: Introductionmentioning
confidence: 99%